2023
DOI: 10.1165/rcmb.2022-0159oc
|View full text |Cite
|
Sign up to set email alerts
|

An Inhibitory Function of TRPA1 Channels in TGF-β1–driven Fibroblast-to-Myofibroblast Differentiation

Abstract: Transient receptor potential ankyrin 1 (TRPA1) is a non-selective Ca 2+ permeable cation channel, which was originally cloned from human lung fibroblasts (HLFs). TRPA1-mediated Ca2+ entry is evoked by exposure to several chemicals, including allyl isothiocyanate (AITC), and a protective effect of TRPA1 activation in the development of cardiac fibrosis has been proposed. Yet, the function of TRPA1 in transforming growth factor β1 (TGF-β1)-driven fibroblast to myofibroblast differentiation and the development of… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…showed that PAI-1 modulated neutrophil efferocytosis and served as a “don't eat me” signal for viable and apoptotic neutrophils 22 . PAI-1 is also an important regulator of fibrosis 23 . However, due to the limitations of this acute disease model, we did not find a change in the levels of TGF-β, a profibrotic cytokine involved in the progression of intestinal fibrosis in IBD 24 , 25 .…”
Section: Discussionmentioning
confidence: 99%
“…showed that PAI-1 modulated neutrophil efferocytosis and served as a “don't eat me” signal for viable and apoptotic neutrophils 22 . PAI-1 is also an important regulator of fibrosis 23 . However, due to the limitations of this acute disease model, we did not find a change in the levels of TGF-β, a profibrotic cytokine involved in the progression of intestinal fibrosis in IBD 24 , 25 .…”
Section: Discussionmentioning
confidence: 99%
“…These transfigured mesenchymal cells gain the ability to proliferate, migrate, and secrete fibrotic factors, particularly collagen variants unique to this ailment. This cascade leads to an anomalous surge in fibrous connective tissue and collagen synthesis and deposition, culminating in the formation of lesions characteristic of IPF (Geiger et al., 2023). Our findings demonstrate that BLM significantly escalates collagen production and deposition, thereby exacerbating EMT.…”
Section: Dicussionmentioning
confidence: 99%
“…In this issue of the Journal , Geiger and colleagues (pp. 314–325 ) show that TRPA1 plays a role in profibrotic signaling in human lung fibroblasts (HLFs) ( 9 ). Specifically, an reverse transcriptase–polymerase chain reaction screen revealed that TRPA1 mRNA was downregulated by TGFβ in primary HLFs from normal subjects.…”
mentioning
confidence: 99%